Analisis Strategi Marketing Mix Melalui Minat Beli Terhadap Keputusan Pembelian Sarimbit Alwa Hijab - Mega Indra Buana, Maya; Nani, Nani (TSARWAH, 2023)
The increasing progress of the Muslim fashion world has given rise to increasingly fierce competition in the Muslim design business, thereby stimulating the strength of business actors to really work hard in managing it. The demands of globalization provide many opportunities for the business world to develop into better quality and be able to meet customer demands. The marketing mix is ​​a company strategy to boost consumer interest and purchasing decisions that result in sales. The aim of this research is to determine the influence of the marketing mix on purchasing decisions for Sarimbit Alwa Hijab through interest both directly and indirectly. The research method is quantitative research with data analysis techniques through path analysis. The research results directly show that the marketing mix has a significant positive effect on purchasing interest, the marketing mix has a significant positive effect on purchasing decisions. Purchase interest does not have a significant effect on purchasing decisions. Meanwhile, the indirect influence of the marketing mix through purchasing interest does not have a significant influence on purchasing decisions.